Resistance Analysis of Rescue Boat in Calm Water Condition. Issue 1 (January 2021) - Utama, I K A P; Sutiyo,; Suastika, I K; Sulisetyono, A; Hasanudin,; Hermawan, Y A; Aryawan, W D
Abstract: Search and rescue operations, especially in ship accidents, require speed and reliability from the rescue vessels in facing the challenges of extreme weather and sea waves. A rescue boat hydrodynamic performance study is very important to be carried out in order to determine the ship's ability to withstand dangerous conditions while in operation. A combination of using Maxsurf and CFD method are implemented to estimate the resistance of 3 (three) selected designs of crew boat, which demonstrated a good agreement between the two techniques. Selection of the final design also uses seakeeping criteria, i.e. having lower pitching and rolling responses. The final model is further tested in a towing tank belongs to the Institut Teknologi Sepuluh Nopember (ITS) and agrees well with Maxsurf and CFD calculation.